Analisis Pendapatan Asli Daerah dan Pengaruhnya Terhadap Belanja Daerah di Provinsi Jambi - M Zahari MS (Ekonomis: Journal of Economics and Business, 2020)
Local Own Revenue (PAD) is an important source for the formation of regional finances to be allocated for regional expenditure. This study aims to analyze the potential sources of regional own-source revenues and their effects on capital expenditure in Jambi Province. This research was conducted in Jambi Province. The data used in the form of secondary data in the period 2010 – 2018. The research method uses descriptive and quantitative methods. The analytical tool used in this study is a simple linear regression analysis and hypothesis testing with t test. The results showed that the potential source of PAD came from local taxes, which provided the largest contribution in realizing PAD, while the smallest contribution was regional retribution. Empirically, the original regional income has a significant influence on regional expenditure, meaning that the higher the PAD income, the higher the regional expenditure for regional development activities and public services.